2014
DOI: 10.3109/09273948.2014.950384
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Cytomegalovirus Uveitis in Immunocompetent Patients

Abstract: There is a spectrum of clinical manifestations of CMV anterior uveitis. A high index of suspicion of a possible viral etiology, especially CMV, and subsequent accurate identification of the virus involved are fundamental to the overall therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…Among immunocompromised patients-especially those with an organ transplant, chemotherapy, or AIDS-the reactivation of virus causes life-threatening diseases, such as gastroenteritis, encephalitis, pneumonitis, and graft rejection (5)(6)(7). In addition, HCMV infection is also implicated in widespread ocular damage and potential vision loss from retinitis, anterior uveitis, and corneal endotheliitis (8)(9)(10)(11). Because HCMV infection of the iris is a risk factor during anterior uveitis, understanding the dynamics of viral infection at the molecular level becomes relevant for understanding the viral pathogenesis in general and developing novel strategies to prevent blindness.…”
mentioning
confidence: 99%
“…Among immunocompromised patients-especially those with an organ transplant, chemotherapy, or AIDS-the reactivation of virus causes life-threatening diseases, such as gastroenteritis, encephalitis, pneumonitis, and graft rejection (5)(6)(7). In addition, HCMV infection is also implicated in widespread ocular damage and potential vision loss from retinitis, anterior uveitis, and corneal endotheliitis (8)(9)(10)(11). Because HCMV infection of the iris is a risk factor during anterior uveitis, understanding the dynamics of viral infection at the molecular level becomes relevant for understanding the viral pathogenesis in general and developing novel strategies to prevent blindness.…”
mentioning
confidence: 99%
“…Moreover, additional antibodies specific to herpes simplex virus (8 eyes), cytomegalovirus (2 eyes), and varicella zoster virus (1 eye) were detected in 11 of the eyes with Fuchs heterochromic iridocyclitis (Ruokonen et al, 2010). Another study found that 3 of 16 patients with anterior uveitis and detectable aqueous cytomegalovirus DNA had clinical features consistent with Fuchs heterochromic iridocyclitis (Woo et al, 2014).…”
Section: Ocular Infectionsmentioning
confidence: 93%
“…62 It is likely that PCR testing from ocular fluids will become helpful in the diagnosis of a variety of emerging infections causing uveitis, such as chikungunya and West Nile virus. 8 …”
Section: Infectious Uveitismentioning
confidence: 99%